2022
DOI: 10.1103/physrevlett.129.036601
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Two-Dimensional Disordered Wigner Solid

Abstract: The interplay between the Fermi sea anisotropy, electron-electron interaction, and localization phenomena can give rise to exotic many-body phases. An exciting example is an anisotropic two-dimensional (2D) Wigner solid (WS), where electrons form an ordered array with an anisotropic lattice structure. Such a state has eluded experiments up to now as its realization is extremely demanding: First, a WS entails very low densities where the Coulomb interaction dominates over the kinetic (Fermi) energy. Attaining s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…For example, in 2D, due to the interplay of the electron-electron (e-e) interaction, the localization phenomena and the Fermi sea anisotropy, anisotropic disordered Wigner crystal has been predicted [7] and some of its signatures has been observed [8]. In 1D, disordered zigzag configurations produced by weakening the 1D confinement and by allowing the electrons to relax in a second dimension has been also reported [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2D, due to the interplay of the electron-electron (e-e) interaction, the localization phenomena and the Fermi sea anisotropy, anisotropic disordered Wigner crystal has been predicted [7] and some of its signatures has been observed [8]. In 1D, disordered zigzag configurations produced by weakening the 1D confinement and by allowing the electrons to relax in a second dimension has been also reported [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Another system that forms a 2D crystal state that can be driven is electron solids or Wigner crystals [42][43][44][45][46][47][48][49][50][51][52][53]. Solid state systems hosting Wigner crystals usually contain some form of quenched disorder, and a variety of studies have revealed nonlinear transport and possible depinning thresholds [44-46, 48, 54] associated with enhanced noise [51].…”
Section: Introductionmentioning
confidence: 99%
“…Of the numerous classical charged systems that form lattice states due to Coulomb interactions, the best known is Wigner crystals of 2D electrons at low densities [29,31,32], which can form in elections on liquid helium [54,55] or in solid-state systems [30,[56][57][58][59][60][61][62][63][64][65]. There have been several studies of 2D Wigner crystals coupled to 1D or quasi-1D nanostructured channels or arrays [66][67][68][69][70][71], while more recently, Wigner crystals coupled to 2D periodic substrates have been studied in moiré heterostructures [72][73][74][75][76][77][78] and dichalcogenide monolayers [79].…”
Section: Introductionmentioning
confidence: 99%